Thermal energy storage characteristics of binary molten salt nanofluids: Specific heat and latent heat - Lee, Daehyeong; Jo, Byeongnam (International Journal of Energy Research, 2021)
This study aims to examine the thermal energy storage characteristics, in terms of specific heat and latent heat, of nanoparticle-doped binary molten salt nanofluids. Two different binary molten salt mixtures, namely carbonate salts (Li2CO3 and K2CO3) and nitrate salts (NaNO3 and KNO3), were used as base solvents. Graphite nanoparticles were dispersed into the salt mixtures. The chemical compositions (molar fractions) of the two salt components were varied from hypoeutectic to hypereutectic, including eutectic compositions, to investigate their effects on the specific heat and latent heat of both the pure salts and their nanofluids. The specific heat of the carbonate salt nanofluid was enhanced, irrespective of the chemical composition, and the enhancement was proportional to the nanoparticle concentration. However, the specific heat of the nitrate salt nanofluid was decreased by the addition of 0.1 wt% of graphite nanoparticles and increased by the addition of a larger amount of 1 wt%. The latent heat of the nanofluids was enhanced by doping nanoparticles into the salt mixtures and was affected by the chemical composition of the solvent salt mixtures. The distinct behaviors of specific heat and latent heat obtained in this study were discussed based on a compressed liquid (solid-like) layer formed near the nanoparticles. The thermal energy storage capacities of the nanofluids were estimated and compared by using their specific heat and latent heat.
Keywords: Carbonate salts; Chemical compositions; Compressed liquid; Doping nanoparticles; Eutectic composition; Molar fractions; Molten salt mixtures; Nanoparticle concentrations; chemical composition; molten salt; nanofluid; specific heat; thermal energy storage